Pelatihan Sistem Informasi Aplikasi Pencatatan Informasi Keuangan (SIAPIK) untuk Peningkatan Kapasitas Pencatatan Keuangan Rumah Cokelat Lung Anai (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Rumah Cokelat Lung Anai is a Micro, Small, and Medium Enterprise (MSME) located in Lung Anai Village and managed by the Dayak Kenyah Community. The financial transaction recording system of Rumah Cokelat Lung Anai is still maintained manually and has not been properly documented. A digital financial application is needed to assist the enterprise in recording financial transactions and preparing financial reports. This community service program aimed to enhance the financial record-keeping capacity of Rumah Cokelat Lung Anai through the implementation of the Financial Information Recording Application System (SIAPIK). The program consisted of socialization, training, and mentoring activities. The results showed that participants gained an understanding of the important role of MSMEs in the economy, financial planning, manual financial record-keeping, and the use of the SIAPIK application. The managers of Rumah Cokelat Lung Anai were also able to practice creating a business account in SIAPIK and complete simulations of financial transaction data entry. The main challenge encountered was the incomplete availability of historical records. Ongoing mentoring continues to be provided to further improve the enterprise’s management capacity.